The score takes care of itself my philosophy of leadership - Walsh, Bill. (New York Portfolio, 2009)
The last lecture on leadership by the NFL's greatest coach: Bill Walsh Bill Walsh is a towering figure in the history of the NFL. His advanced leadership transformed the San Francisco 49ers from the worst franchise in sports to a legendary dynasty. In the process, he changed the way football is played. Prior to his death, Walsh granted a series of exclusive interviews to bestselling author Steve Jamison. These became his ultimate lecture on leadership. Additional insights and perspective are provided by Hall of Fame quarterback Joe Montana and others. Bill Walsh taught that the requirements of successful leadership are the same whether you run an NFL franchise, a fortune 500 company, or a hardware store with 12 employees. These final words of 'wisdom by Walsh' will inspire, inform, and enlighten leaders in all professions.
Includes index.
Keywords: Leadership